2022
DOI: 10.1038/s41598-022-17285-x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulpal temperature changes during the cementation of ceramic veneers

Abstract: Adhesive cementation of ceramic veneers may increase pulpal temperature (PT) due to the combined effect of heat generated by the curing unit and the exothermic reaction of the luting agent (LA). PT increase may induce pulpal damage. The aim was to determine the PT rise during the luting of ceramic veneers (CV) of different thicknesses with light- or dual-curing (LC, DC) adhesive cements as well as pre-heated restorative resin-based composites (PH-RBC). For this a thermocouple sensor was positioned in the pulp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Furthermore, the application of preheated restorative resins as luting agents resulted in a significantly higher temperature increase compared to that measured for adhesive resin cements." (28) Similarly, Alvarado G et al (2020) stated that pulp temperature rise may even cause pulp damage, however, they indicate that when the preheated resin temperature is at 60° there is no danger of pulp damage. (1) Similarly, Bhopatkar J et al (2022) reported that "placing a composite resin heated to 60°C increases the pulp temperature by 0.8°C, while 15 seconds of light curing increases the pulp temperature by 4.5-5°C", [...] recommending that resin preheating should not exceed 60°C to avoid being harmful.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the application of preheated restorative resins as luting agents resulted in a significantly higher temperature increase compared to that measured for adhesive resin cements." (28) Similarly, Alvarado G et al (2020) stated that pulp temperature rise may even cause pulp damage, however, they indicate that when the preheated resin temperature is at 60° there is no danger of pulp damage. (1) Similarly, Bhopatkar J et al (2022) reported that "placing a composite resin heated to 60°C increases the pulp temperature by 0.8°C, while 15 seconds of light curing increases the pulp temperature by 4.5-5°C", [...] recommending that resin preheating should not exceed 60°C to avoid being harmful.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated a significant temperature increase at the end of the fourth preparation phase in the control group (without medium), and the following rinsing was not able to reduce the temperature below the potentially harmful threshold. Although several thermal conductive mediums, such as silicone impression material [14,15], alginate impression material [13], ultrasound, or echo-transmission gel [34], were used in other studies, none of them were able to account for all the mechanisms by which heat is dissipated in vivo.…”
Section: Discussionmentioning
confidence: 99%